How You Move Is What I See: Planning an Action Biases a Partner’s Visual Search - Dötsch, Dominik; Vesper, Cordula; Schubö, Anna (Frontiers in Psychology, 2017)
Activating action representations can modulate perceptual processing of action-relevant dimensions, indicative of a common-coding of perception and action. When two or more agents work together in joint action, individual agents often need to consider not only their own actions and their effects on the world, but also predict the actions of a co-acting partner. If in these situations the action of a partner is represented in a functionally equivalent way to the agent’s own actions, one may also expect interaction effects between action and perception across jointly acting individuals. The present study investigated whether the action of a co-acting partner may modulate an agent’s perception. The “performer” prepared a grasping or pointing movement towards a physical target while the “searcher” performed a visual search task. The performer’s planned action impaired the searcher’s perceptual performance when the search target dimension was relevant to the performer’s movement execution. These results demonstrate an action-induced modulation of perceptual processes across participants and indicate that agents represent their partner’s action by employing the same perceptual system they use to represent an own action. We suggest that task representations in joint action operate along multiple levels of a cross-brain predictive coding system, which provides agents with information about a partner’s actions when they coordinate to reach a common goal.